A critical literature review of the effectiveness of various instruments in the diagnosis of dementia in adults with intellectual disabilities. Issue 1 (29th June 2016) - Elliott‐King, Jordan; Shaw, Sarah; Bandelow, Stephan; Devshi, Rajal; Kassam, Shelina; Hogervorst, Eef
Abstract: Introduction: Currently, there is no consensus on dementia diagnostics in adults with intellectual disabilities (ID). There are three types of assessments available: direct cognitive tests, test batteries, and informant reports. Methods: A systematic literature search was conducted in four databases yielding 9840 records. Relevant studies were identified and selected using predefined inclusion and exclusion criteria and then coded and classified according to assessment type. This was completed by two independent researchers, with a third consulted when discrepancies arose. The review collates diagnostic instruments and presents strengths and weaknesses. Results: Overall 47 studies met the search criteria, and 43 instruments were extracted from the selected studies. Of which, 10 instruments were classified as test batteries, 23 were classified as direct cognitive tests, and the remaining 10 were informant reports. Discussion: This review can recommend that cognitive test batteries can offer the most practical and efficient method for dementia diagnosis in individuals with ID.